Transformasi Pengelolaan Klub Sepakbola Di Indonesia - -, Sulistiyono (Universitas Negeri Semarang, 2012)
Professionalism management of a football club is a challenge that must be faced by all managers of football clubs in Indonesia if every club aims to achieve performance. AFC (Asian Football Confederation) implement projects to professionalize the management of clubs and competitions countries in Asia who want to appear in the Asian Champions League began in 2012. The project began in 2008 socialized. The results of the assessment by AFC, competitions and clubs in Indonesia does not meet a minimum standard score of professional football management. Changes to the professional management should be guided by a professional club management standards issued by the AFC. Amateur clubs in particular division I should be prepared to make changes to the management model that has been done, the changes should be made in the event include: club funding, organizational status, professionalism the entire staff of the organization. This is done because the division is a club that I have a chance and change management model if it passes the main division level. The source of funding can be explored through club sponsorship, merchandise sales, contracts with media, optimizing the role of government in helping the supporting infrastructure particularly related to public access.